UJI STABILITAS FISIK SEDIAAN SERBUK INSTAN DENGAN KOMBINASI JAHE, TEMULAWAK, KUNYIT DAN SEREH - Husnani Husnani; Rissti Zulfitri (Jurnal Komunitas Farmasi Nasional, 2022)
Instant powder drink is a drink made from fresh or dry ingredients that are boiled for less than 60 minutes, then added sugar or without sugar and the water is evaporated until sugar crystals or powder are obtained. This study aims to determine the physical stability of instant powder drinks with the composition of ginger, ginger, turmeric, lemongrass and sugar. The physical stability test of instant powder was carried out at room temperature for one month, namely at 0, 7, 14, 21 and 28 days. The parameters observed included dissolving time, pH, water content and organoleptic tests including color, aroma and taste. The results showed that the instant powder drink preparation can be said to be stable from 5 weeks of observation on days 0, 7, 14, 21, 28. The results showed that the instant powder drink preparation on the evaluation of the water content test, dissolving time test, organoleptic test, and pH meter test met the standard requirements for instant powder drinks.